Analisis Kadar Timbal (Pb) Darah dan Malondialdehid (MDA) Pada Manusia Silver di Kota Semarang - Umi Rosidah; Ichsan Hadipranoto (Poltekkes Kemenkes Semarang, 2023)
The danger of lead in paint that is coated on the human body, silver can enter through the skin and will interact with proteins, DNA, RNA and oxidative stress. Formation of Reactive Oxygen Species (ROS) by lead can cause oxidative stress and is characterized by an increase in the enzymes catalase, malondialdehyde (MDA) and Oxidized glutathione (GSSG). The aim of this study was to analyze blood lead levels against Malondealdehyde (MDA) in silver humans in Semarang City. This study used an observational analytic study with a cross sectional approach to analyze the effect of lead levels on Malondialdehyde levels in silver humans in Semarang City using a t test to see differences in results based on length of work, length of exposure and age on lead levels, and the effect of lead on MDA. The results showed that from 20 human samples, the lowest lead level was 23.9 g/dl and the highest was 61.9 g/dl with an average blood lead level of 37.3 g/dl with an average blood lead level of 37.3 g/dl, and the lowest MDA level was 0.4 mg/L and the highest level is 1.74 mg/L with an average of 1.2 mg/L. Based on the data obtained from the t test, it shows a significant value (P-Value) of 0.610 which means > 0.05, this indicates that the decision taken is to reject H1 which means that there is no effect between the results of lead levels on the results of MDA levels.